The requirements and compliance of the Finnish act on energy efficiency in a large enterprise : a case study from the healthcare industry - Peltonen, Anniina (2015)
Energy management is becoming increasingly important for organizations due to legislative, environmental, and economic causes. The Act on Energy Efficiency came into force in Finland on 1st January 2015. One of the law’s obligations requires large enterprises to enhance and report their energy efficiency performance with an energy audit every four years. However, a large company can be exempted from the energy audit obligation in three ways under the Finnish law. The aim of this study is to discover the best solution for the target organization to meet the obligations posed by The Act on Energy Efficiency. The options considered in this study are: 1) performing energy audit as the law requires, 2) implementing and certifying EES+ energy management system with the ISO 14001 environmental management system in place, and 3) implementing a non-certified EES+ with the voluntary energy efficiency agreement. Previous research has widely studied environmental and quality management systems. However, energy management systems are a more recent phenomenon where little research is conducted. Moreover, research on integrating environmental and energy management systems appears to be non-existent which indicates a clear research gap in the field. This research was conducted as a qualitative case study. Data mainly consists of the law’s and EES+ system’s requirements, and the target company’s internal material. The analysis was conducted utilizing content analysis method, but also comparative analysis was applied when comparing the options’ requirements and measures needed. The results of this study clearly indicate that the most suitable option for the target organization is to implement the uncertified EES+ system with the voluntary energy efficiency agreement. However, as the target organization has already the ISO 14001 environmental management system in place, it would seem more reasonable to integrate the EES+ into the existing ISO 14001 instead of having two separate management systems.